Konsep Pendidikan Islam dalam Perspektif Al-Quran (Tinjauan Metode Pendidikan Islam dalam Surat Huud: 1-4) - Firmansyah (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2020)
One of the weaknesses of the implementation of Islamic education in schools is that the learning activities of Islamic Religious Education (PAI) are less attractive, tend to be monotonous, only using the lecture method. This is because Islamic Education Teachers are less willing to explore various methods, including from the Al-Quran and hadith, which might be applied in the Islamic education learning process in schools. This study strengthens various previous studies which also raise the theme of the concept of Islamic education in the perspective of the Al-Quran. However, the research that examines the concept of Islamic education in the Surah Huud: 1-4, after doing online and printed literature searches, has not been found by the author. Therefore, this study can be said to be different from previous research. This research is considered to be contributive, offering alternative educational methods that are explored from the Surah Huud: 1-4. For this reason, this study discusses the concept of education and educational methods contained in the Surah Huud: 1-4. By using library research methods with descriptive qualitative analysis techniques, it can be concluded that the concept of Islamic education is long life education, which contains the main material content of Islamic education, starting with the concept of worship to Allah Swt (aqidah), then proceed with material in the field of shari'ah, then muamalah (morals) to achieve the ultimate goal of Islamic education, to achieve true happiness, namely avoiding the torment of hell (being put into heaven). In Surah Huud: 1-4, there are at least five learning methods in Islamic education: (1) tafshiil method, (2) tabsyiir method, (3) tandziir method, (4) targhiib method, and (5) tarhiib method. The application of these methods in Islamic education is a complementary unit.